2002
DOI: 10.2151/jmsj.80.213
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Circulation over East Asia during El Nino Episode in Northern Winter, Spring and Autumn.

Abstract: Diagnostic analysis is made to investigate features of the moisture circulation over East Asian during the El Niñ o episode in northern winter, spring and autumn. It is found that in all these seasons, the anomalies of precipitation in China, atmospheric precipitable water, water vapor transport and moisture divergence over East Asia in the El Niñ o mature phase, differ from those in the rest of the phases. In the El Niñ o mature phase, positive precipitation anomalies occur in the southern part of China. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 27 publications
11
99
0
4
Order By: Relevance
“…This result is consistent with the previous findings (e.g., Chang et al 2000;Chia and Ropelewski 2002;Zhang and Sumi 2002). The ENSO-spring rainfall relationship in Taiwan can be summarized in terms of the PSH variability as follows.…”
Section: Variability Of the Pacific Subtropical Highsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the previous findings (e.g., Chang et al 2000;Chia and Ropelewski 2002;Zhang and Sumi 2002). The ENSO-spring rainfall relationship in Taiwan can be summarized in terms of the PSH variability as follows.…”
Section: Variability Of the Pacific Subtropical Highsupporting
confidence: 92%
“…During a strong El Niño event, the appearance of an anomalous lower-level anticyclone over the Philippine Sea and the intrusion of a weak midlatitude front system into the eastern coastal areas of China are jointly responsible for the more frequent occurrence of heavy rainfall events and more amount of rainfall in Taiwan. The anomalous Philippine Sea anticyclone (PSAC; Wang et al 2001;Wang and Zhang 2002) induces anomalous warm southwesterly flows to enhance moisture transport from the South China Sea into Taiwan and central China, leading to intensified moisture convergence and rainfall activities over there (e.g., Tian and Yasunari 1998;Chang et al 2000;Zhang and Sumi 2002). East Asia tends to be warmer in winter and wetter in spring during a strong El Niño event (e.g., Ropelewski and Halpert 1987;Tomita and Yasunari 1996;Zhang et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang & Sumi (2002) showed that there are positive precipitation anomalies in winter over southern areas of China during the mature phase of El Niño. The ENSO often develops into a mature phase in boreal winter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicates that tropical Pacific SST anomalies in relation to ENSO can affect winter rainfall over South China (Zhang et al, 1999;Wang et al, 2000;Zhang and Sumi, 2002;Wu et al, 2003;. Above-normal (below-normal) rainfall is (Wang et al, 2000;Wu et al, 2003).…”
Section: Removal Of Enso Impactsmentioning
confidence: 98%